Volar Locking Plating of Extra-articular Distal Radius Fracture: A Retrospective Clinical Study Comparing Locking Screws versus Smooth Locking Pegs - Tordjman, Daniel; Younis, Mohammad; Factor, Shai; Eisenberg, Gilad; Atlan, Franck; McBeth, Jessica; Pritsch, Tamir; Rosenblatt, Yishai (Journal of Wrist Surgery, 2023)
Background Open reduction and internal fixation of distal radius fractures is one of the most common procedures performed in wrist surgery. The use of volar locking plate has gained increasing interest in the past decade. Epiphyseal fixation can be done either with locking screws or smooth locking pegs, with no evidence supporting the use of one rather than the other.Purpose The aim of this study is to compare the stability of distal radius fixation by volar locking plate using locking screws or smooth locking pegs.Methods Adult patients with A2–A3 AO fractures treated with a volar plate with locking screws only or smooth locking pegs only were retrospectively included. Radiographic assessment was performed to evaluate extra-articular parameters in the intraoperative postreduction and fixation period and after bony healing. Forty-seven distal radius fractures were included.Results Twenty-four fractures had fixation with locking screws and 23 had fixation with smooth locking pegs. For both groups, all radiographic parameters measured showed a statistically significant difference between the intraoperative postreduction and fixation period and the remote postoperative period after union of the fracture (p < 0.05) attesting a slight loss of reduction. Nevertheless, there were no significant differences between the groups in radiographic extra-articular parameters.Conclusion This clinical study shows that there is no difference in stability fixation between locking screws or smooth locking pegs in A2–A3 distal radius fractures.Clinical Relevance The use of smooth locking pegs only for epiphyseal fixation appears to be safe in volar plating of A2–A3 distal radius fractures in adult patients and could be an alternative to locking screws. More clinical data are needed to confirm these results.Level of Evidence Level III; retrospective comparative study.
Keywords: distal radius fracture; extra-articular; volar locking plate; smooth locking peg; locking screw